Experimental and Numerical Evaluation of Mechanical Properties for Carbon Fiber Reinforced Epoxy LY5052 Composite for Prosthesis Structures - Mahfud Ibadi; Yudan Whulanza; Herry Purnomo (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2022)
Carbon Fiber Reinforced Epoxy is one of the materials that is widely used in the manufacture of phosthesis structures. In this study, the carbon fiber used carbon-kyoto type plain weave while the epoxy matrix was LY5052. The maximum stress (s) from the tensile test is 537.15 MPa. Furthermore, tensile test simulation with Finite element analysis simulation using Abaqus software, in the process the selection of mesh through input sizing control determines the accuracy of the results. The simulation results are 523.3 MPa when compared to the experiment the difference is 2.58%